The adolescents having substance disorder applying to treatment çenter via probation, health policy and family: similar? different? - Yüncü, Zeki; Başay, Ömer; Altıntoprak, Ender; Coşkunol, Hakan; A. Akgür, Serap; Aydın, Cahide (Journal of Dependence, 2010)
Objective: Sentencing the children, who are substance abusers, with heavy imprisonment will not be an effective way of protection. Taking on the children's substance abuse matters by the social security and help associations rather than the criminal courts will be a healthy attitude. Probation (P) and the health policy (HP) are among these practices. The similarities and the differences of the cases applying via P, HP and FS (family support) have been assessed in this study.Methods: The file records of the cases applied to an addiction center towards the children and adolescents having substance disorder, between January 2005 and December 2007 have been reviewed. It has been determined that 326 cases have applied to the center in this period. It has been determined that 16 of these cases P (4.9 %) scope and 16 of them have been assessed within the HP (4.9 %) scope. The cases, who applied via family (n=16) have been appointed randomly. SPSS 13.0 program has been used for the statistical assessment.Results: It has been found that the differences among the groups are statistically meaningful in terms of onset age and the early onset age belongs to the cases having FS (p
Keywords: Probation; adolescent; drug use